Book Review : Growing Up in a Divided Society - Hayes, Grahame (PINS-Psychology in Society, 2025)
The brutality of South African society in the present political conjuncture forces memories upon our consciousness that might otherwise become part of our social amnesia. However, a 'memory' that has by and large escaped our social and political consciousness is the 'contexts of childhood'. The campaigns around the plight of detained children and the general publicisation, from the left predominantly, of the problems facing children and their families in the townships since October 1984, have to some extent rehabilitated our memories about the childhood contexts of social struggles. "Growing up in a divided society", edited by Sandra Burman and Pamela Reynolds is therefore a most timely and welcome reminder about the contexts and repression of childhood in the social struggles of many communities in South Africa at the moment.